Analysis photo of the year 2006 Indonesian press photo award based on the three visual layers theory - Prasetyo, Andry; Guntur, Guntur; Ajidarma, Seno Gumira; Soewarlan, Santosa (Gelar: Jurnal Seni Budaya, 2024)
This article aims to analyze the work of the 2016 Indonesian Press Photo Award Photo of the Year entitled "Tinjau Titik Api," using the "Three Visual Layers" theory. Photo of the Year 2016 was chosen because it has the advantage of good visual value and high news value, especially for people in the news. The three visual layers analysis includes optical, cultural, and photographic meaning. The optical aspect is for the non-blind eyes, the cultural aspect includes known visual appearances and unknown visual appearances, and the photographic aspect has a functional appearance, personal appearance, and subjective appearance. The research method is qualitative analysis because its implementation is based on visual analysis to find meaning from photos depicting three figures who are symbols of the strength of the Indonesian state, namely, the President of the Republic of Indonesia, Joko Widodo, TNI Commander General Gatot Nurmantyo, and Chief of the Indonesian National Police General Badarudin Haiti, who is inspecting the location of forest and land fires, in Geronggong Village, Ogan Komering Ilir Regency, South Sumatra. Data analysis involves: Scrutinizing relevant and irrelevant information, reducing data, compiling codes against findings data, and verifying codes as a reference for discussion and conclusion. The research results show that the 2016 Photo of the Year contains meaning that shows the Indonesian government's commitment to dealing with forest and land fires in Sumatra. The photo has advantages in terms of visual value which is reflected in the composition, depth of focus, and expression of the president, and in terms of news value, it is superior in terms of character value, as well as another advantage in the closeness of the photographer to the object of the event.